The Oxford handbook of religion and ecology - Gottlieb, Roger S. (Oxford University Press, 2006)
The last two decades have seen the emergence of a new field of academic study that examines the interaction between religion and ecology. This handbook serves as an overview of these exciting new developments. Part one explores traditional religious concepts of and attitudes towards nature and how these have been changed by the environmental crisis. Part II looks at larger conceptual issues that transcend individual traditions. Part III examines religious participation in environmental politics.